'Magis corde quam organo': Agazzari, Amadino, and the hidden meanings of Eumelio. (15th July 2020) - Lyon, Elizabeth L
Abstract: Some time after Christmas 1605, Agostino Agazzari (1578–1640) was asked to provide music for a pastoral drama, Eumelio ; it was performed a month later during Carnival at the Jesuit-run Seminario Romano. In the preface to the subsequently published score (Venice: Amadino, 1606), Agazzari tells his readers that he agreed to the commission 'because of the beautiful and useful allegory that I saw in [the libretto]'. What this beautiful and useful allegory was, however, has not been apparent to modern scholars. Margaret Johnson goes so far as to write that 'It is perhaps unfortunate that Agazzari even mentioned the presence of a moral; it might otherwise have been overlooked, since its presence is obtrusive only in the composer's preface'. This article offers an interpretation of the allegory of Eumelio by reading the opera as a commentary on the musical and spiritual teachings of Council of Trent, to which the printer's mark of Agazzari's publisher, Ricciardo Amadino, paratextually alludes. Although Amadino was the printer of some of the most famous prints of the Seicento (including Monteverdi's Orfeo and Fifth Book of Madrigals), his printer's mark and motto, 'more with the heart than with the organ', has not been commented upon in modern scholarship. The motto's possible sources and its contemporary resonances and meanings point to an understanding of Eumelio as an allegory of Christian soteriology and the Christian musician. The opera externalizes and dramatizes the kinds of inner examination that many believed were incumbent on musicians in a post-Trent musico-religious culture. As a performed and printed work, then, Eumelio gave musicians pause to reflect on their inner lives, the purpose of their musical activities, and the kinds of motivations they acted upon in performance.